(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Three-fourths of the world’s population uses 30% of all plant species as a safe source of disease control and treatment. Similarly, Solanum nigrum (Black nightshade), a therapeutic herb with small, spherical berry fruits, is used as an herbal remedy to treat many different diseases, including respiratory diseases. According to recent research, this plant can aid in the management of COVID-19. Alkaloids, flavonoids, steroids, glycoproteins, tannins, polysaccharides, polyphenolic compounds etc. are found in this plant. Among them, polyphenolic compounds are mostly responsible for showing various pharmacological activity. Anti-tumor, antioxidant, anti-diabetic, anti-inflammatory, anti-seizure, immunostimulant, hepatoprotective, antimicrobial activities are shown by S. nigrum according to multiple studies. The aim of this article is to compile different aspect of this plant like plant description, uses, chemical constituents, pharmacological activities and especially its role in the management of COVID-19 and probable mechanism behind this role. J. Asiat. Soc. Bangladesh, Sci. 49(2): 237-263, December 2023